THE SPATIO-TEMPORAL DYNAMIC IN WATER NEAR PALABUHAN RATU COAL FIRE PLANT, SUKABUMI, WEST JAVA - Niken Anissa Putri; Masita Dwi Mandini Manessa; Hafid Setiadi (International Journal of Remote Sensing and Earth Sciences (IJReSES), 2023)
Indonesia Power PLTU Jabar 2 Palabuhanratu's activities have an impact on the quality of the surrounding river water and ocean. Monitoring the quality of the water thereafter became an important factor. Using remote sensing technologies, the spatial and temporal sea surface temperature and chlorophyll-a of water can be determined. This study aims to (1)  ; (2)  ; and (3)  . River water and ocean quality, including physical parameters (total dissolved solids, electrical conductivity, and temperature) and chemical parameters (pH and salinity). (1) River water and saltwater quality in the Cimandiri Downstream River and Batu Bintang Beach are suitable with regard to physical parameters (total dissolved solids, electrical conductivity, and temperature) and chemical parameters (pH and salinity). (2) According to Health Ministerial Regulation No. 32/2017 and Government Regulation No.22/2021, the river and seawater quality in the Cimandiri Downstream River and Batu Bintang Beach for clean water is adequate in terms of physical characteristics (total dissolved solids, electrical conductivity, and temperature) and chemical parameters (pH and salinity). (3) The average Salinity from August through November of 2021 was 20.76 ppt, 16.25 ppt, 15.76 ppt, and 18.51 ppt. The average Salinity between April and July of 2022 was -2.74 ppt, 3.51 ppt, 0.51 ppt, and 4.25 ppt.